Diagnostics and treatment of internal diseases in the elderly (gastroenterology, pulmonology, hematology) - Syvolap, V. D.; Bogoslav, T. V.; Сиволап, Віктор Денисович; Богослав, Тетяна Вікторівна (Запорізький державний медичний університет, 2020)
The training manual was prepared in accordance with the requirements of the new program of the discipline "Internal Medicine" for higher medical schools of III-IV levels of accreditation, approved by the Ministry of Health of Ukraine (2016). The manual contains training materials on the topic "Diagnostics and treatment of internal diseases in the elderly." The physiological changes in the aging digestive, respiratory, blood and blood-forming organs, the features of diagnostics and treatment in the elderly, the pharmacokinetics and pharmacodynamics of medications are highlighted. The methodological and educational materials presented in the manual will allow students not only to learn the basic gerontological aspects in the clinic of internal diseases, but also to gain practical skills in the supervision in elderly patients.
Keywords: internal medicine; internal diseases in the elderly